DR-CONTRACT: an architecture for e-contracts in defeasible logic. (19th January 2010) - Governatori, Guido; Pham, Duy Hoang
We introduce the DR-CONTRACT architecture to represent and reason on e-contracts. The architecture extends the DR-device architecture by a deontic defeasible logic of violation. We motivate the choice for the logic and we show how to extend RuleML to capture the notions relevant to describe e-contracts for a monitoring perspective in defeasible logic.